Toxicogenomic responses of Caenorhabditis elegans to pristine and transformed zinc oxide nanoparticles. (April 2019) - Starnes, Daniel; Unrine, Jason; Chen, Chun; Lichtenberg, Stuart; Starnes, Catherine; Svendsen, Claus; Kille, Peter; Morgan, John; Baddar, Zeinah Elhaj; Spear, Amanda; Bertsch, Paul; Chen, Kuey Chu; et al.
Abstract: Manufactured nanoparticles (MNPs) undergo transformation immediately after they enter wastewater treatment streams and during their partitioning to sewage sludge, which is applied to agricultural soils in form of biosolids. We examined toxicogenomic responses of the model nematode Caenorhabditis elegans to pristine and transformed ZnO-MNPs (phosphatized pZnO- and sulfidized sZnO-MNPs). To account for the toxicity due to dissolved Zn, a ZnSO4 treatment was included. Transformation of ZnO-MNPs reduced their toxicity by nearly ten-fold, while there was almost no difference in the toxicity of pristine ZnO-MNPs and ZnSO4 . This combined with the fact that far more dissolved Zn was released from ZnO- compared to pZnO- or sZnO-MNPs, suggests that dissolution of pristine ZnO-MNPs is one of the main drivers of their toxicity. Transcriptomic responses at the EC30 for reproduction resulted in a total of 1161 differentially expressed genes. Fifty percent of the genes differentially expressed in the ZnSO4 treatment, including the three metal responsive genes ( mtl-1, mtl-2 and numr-1 ), were shared among all treatments, suggesting that responses to all forms of Zn could be partially attributed to dissolved Zn. However, the toxicity and transcriptomic responses in all MNP treatments cannot be fully explained by dissolved Zn. Two of the biological pathways identified, one essential for protein biosynthesis (Aminoacyl-tRNA biosynthesis) and another associated with detoxification (ABC transporters), were shared among pristine and one or both transformed ZnO-MNPs, but not ZnSO4 . When comparing pristine and transformed ZnO-MNPs, 66% and 40% of genes were shared between ZnO-MNPs and sZnO-MNPs or pZnO-MNPs, respectively. This suggests greater similarity in transcriptomic responses between ZnO-MNPs and sZnO-MNPs, while toxicity mechanisms are more distinct for pZnO-MNPs, where 13 unique biological pathways were identified. Based on these pathways, the toxicity of pZnO-MNPs is likely to be associated with their adverse effect on digestion and metabolism. Graphical abstract: Image 1 Highlights: Pristine ZnO-MNPs and ZnSO4 show similar toxicity to Caenorhabditis elegans . Toxicogenomic responses in all treatments are partially explained by dissolved Zn. Transformed ZnO-MNPs show similar in toxicity but different transcriptomic responses. Distinct toxicity pathways are indicated for the phosphatized ZnO nanoparticles. Abstract : The toxicity and transcriptomics responses of transformed ZnO nanoparticles are distinct from pristine ZnO nanoparticles and only partially due to release of ions.